Sexual Violence towards Men: Sexual Violence Judging from Individual Factors of Victims - Tiara Diah Sosialita (Universitas Katolik Soegijapranata, 2019)
This study aims to explore the gender characteristics of the victims of sexual violence, so thatcomprehensive understanding about determinants of sexual violence can be obtained. Gender characteristics allow society to evaluate gender as part of their social role that is devised and related to particular public view that men are seen as an individual with more physical strength and responsibility than women in many various contexts. This study involved five men as victims of sexual violence whom experienced it by their partner in context of intimate relationship. Data collecting used Bem Sex Role Inventory (BSRI) questionnaire within in-depth interview. Result of this study was useful to provide a comprehensive description of mental dynamics according to the occurence of sexual violence. An understanding of sexual violence predictors was expected to reveal the phenomena of sexual violence towards men whereas lack of awareness in our society. Thus, considering the mental dynamics of sexual violence victim was headed us to be able to repeal the stigma related men and masculinity term. Result also revealed that sexual violence have been affected their identity and sexual activities. As the fact about this study, the existence of support system around them was an important help for them to deal and heal their conditon.